Occupational health hazards encountered by nurses at Letsholathebe II memorial hospital in Maun, Botswana - Keorekile, Opelo (University of Limpopo, 2015)
Nurses are an integral component of the health care delivery system and they encounter occupational health problems classified as biological, chemical, physical, and psychosocial hazards. Nurses also face health hazards such as Hepatitis B, Acquired Immune Deficiency Syndrome, tuberculosis, cytotoxic drugs, anesthetic agents, needle stick injury, back pain, and stress. At Letsholathebe II Memorial Hospital in Maun, nurses and other health professionals face occupational health and safety risks at the workplace. Aim and Objectives The aim of the study was to identify the occupational health hazards encountered by nurses at Letsholathebe II Memorial Hospital in Maun, Botswana. The objectives were to identify occupational health hazards at Letsholathebe II Memorial Hospital; determine organic and inorganic disorders caused by occupational health hazards; determine coping mechanisms of nurses towards occupational health hazards and the compliance of nurses to written protocols that address occupational health hazards. Research Method and Design A quantitative descriptive cross-sectional method was adopted. The population comprised 200 nurses employed at Letsholathebe II Memorial Hospital. Simple random sampling was used to select 132 nurses who participated in the study. A self-administered questionnaire was used for data collection. Descriptive and inferential statistics were used for data analysis. Results The study revealed health hazards namely; back aches, frequent headaches, and persistent tiredness; mercury, solvents and anaesthetic gases; HIV, streptococcus, staphylococcus, Hepatitis B and measles. Nurses also reported fatigue, loss of sleep due to stress, anxiety and persistent tiredness. Conclusion The study concluded that nurses at Letsholathebe ll Memorial hospital experienced physical, chemical, biological and psychological health hazards. Recommendations The study recommends that nurses should have access to OHS information, that OHS awareness should be created at Letsholathebe II Memorial Hospital.
Thesis (MPH.) -- University of Limpopo, 2015
Keywords: Occupational Health; Occupational safety; Occupational hazards; 610.736883; Industrial safety -- Botswana; Nurses -- Botswana -- Maun; Hospitals, Public -- Botswana; Medical Services Management